Analysis of Omega-3 Content in Different Cultivation Treatments of Purslane Plants (Portulaca oleracea) - Nurlina Muhammad; Zauzah Abdullatif; Sofyan Samad; Sri Soenarsih DAS (Jurnal Penelitian Pendidikan IPA, 2023)
Purslane is a wild plant that is beneficial for human health. The aim of this research was to analyze the omega-3 content in various purslane cultivation treatments. This research was carried out in October-November 2022 at Wayamiga Village, East Bacan District, South Halmahera Regency, North Maluku Province. The tools used in this research were a scales watering can, a digital camera, a roller meter, a hose, a ruler, a rope, a counter, a plastic bucket, a plastic bag, stationery, hoe. The materials are purslane seeds, chicken manure, cow manure, label paper, and water. Population and Sample. The population in this study was purslane plants (Portulaca oleracea). At the same time, the samples were 27 purslane plant samples planted in 27 seedbeds. Research Variables: 1) The independent variable is the treatment dose of manure. 2) The dependent variable is plant growth with the parameters observed, namely vegetative growth: a) plant height and b) number of branches. Results. The single factor of chicken manure fertilization had an effect on the variable content of plant height and stem diameter of purslane at 30 HST. The single factor: Different harvest times influence the number of branches, stem diameter, and crown diameter of purslane plants which are influenced by differences in harvest time with a harvest time of 45 HST as the best treatment. The interaction between manure fertilization and different harvest times affects the variables of plant height, number of branches, stem diameter, crown diameter, and fresh weight of purslane plants. The best combination is chicken manure and a harvest time of 45 HST. The different treatments in cultivating purslane plants affect the omega-3 content, namely the differences in harvest time and the interaction between manure and differences in harvest time with the best harvest time being 35 HST and the best combination of cow manure and first harvest time